Opti-4TB: A protocol for a prospective cohort study evaluating the performance of new biomarkers for active tuberculosis outcome prediction - Bahuaud, Olivier; Genestet, Charlotte; Hoffmann, Jonathan; Dumitrescu, Oana; Ader, Florence (Frontiers in Medicine, 2022)
Introduction: Tuberculosis (TB) treatment requires the combination of multiple anti-TB drugs during 6 months or more depending on strain drug susceptibility profile. Optimizing the monitoring of anti-TB therapy efficacy is required to provide adequate care and prevent drug resistance emergence. Moreover, accurate monitoring tools are needed for the development of strategies aiming at reducing treatment duration. Opti-4TB is a “proof of concept” study aiming at developing a blood-based monitoring of TB outcome by deciphering host immune signatures associated with latency or disease activity through the combination of “omic” methods. The primary objective is to assess the performances of new biomarkers for TB outcome prediction and to determine specific profiles associated with the outcome of treated TB patients. Methods and analysis: Opti-4TB is a prospective, single center study including adult patients hospitalized for pulmonary TB. A workflow will be set up to study the immune status of 40 TB patients and 20 controls with latent TB infection. Blood samples will be collected at four timepoints: before treatment initiation (V1), at day 15 (V2), at 2 months (V3) and at 6 months (V4). Mtb-specific immune responses will be assessed at each timepoint with three different assays : 1) A whole blood transcriptomic signature assessing the “RISK-6” score; 2) A proteomic signature based on 27 cytokines and chemokines measured in plasma; 3) An immunophenotypic monitoring of circulating T-cell subpopulations using spectral flow cytometry. This in depth characterization of Mtb-specific immune response throughout the treatment, correlated with clinical outcomes, will lay the basis for the elaboration of the most basic and universal stage-specific immune signatures associated with latency, active disease and cure. Ethics and dissemination: Ethical approval has been obtained from the institutional review board (n°69HCL18_0757). Results will be communicated at scientific meetings and submitted for publication in peer-reviewed journals. Trial registration number: NCT04271397.